Factors influencing satisfaction and intention to use Chatbot on purchase intention on E-Commerce Shopee. - Ferdiansyah Hari Saputra; Yudi Sutarso (At-Tadbir : jurnal ilmiah manajemen, 2024)
This research analyses chatbot features on consumer satisfaction regarding intention to use and purchase intention in an e-commerce Shopee. This research also involves consumer satisfaction variables that significantly impact consumer usage and purchase intentions. The data in this research was obtained through a questionnaire from 108 respondents who were sampled and explained using a purposive sampling technique. Using WarpPLS and SPSS to analyze data. The findings in this research show that consumer satisfaction greatly influences purchase intentions and the use of chatbot features in Shopee e-commerce. Further interactivity, communication style, and responsiveness. and perceived ease of use also plays a vital role in influencing consumer satisfaction. The aim of this research is to show that several factors influence consumer satisfaction in using the Shopee chatbot feature, which will significantly impact consumers in deciding their purchase intentions and intentions to use a product when making online purchases via Shopee e-commerce.